Karakter Seleksi Fase Vegetatif Jagung terhadap Hasil pada Cekaman Genangan Air - Syah, Uswah Trywulan; Suwarno, Willy Bayuardi; Azrai, dan Muhammad (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
Maize is an important crop in Indonesia that is utilized for food, feed, and industry. Waterlogging is one of the abioticstresses challenging maize production in recent years due to climate changes. Vegetative-phase screening methods may benefitplant breeding programs because potential genotypes can be identified at earlier stage with lower cost. This study consistedof two experiments. The first experiment was carried out at the Sawah Baru experimental station of Bogor AgriculturalUniversity (IPB), Bogor, from June to September 2017 using an alpha lattice design with three replications and four blockswithin each replication. The second experiment conducted in a greenhouse at Cikabayan experimental station of IPB, Bogor,from December 2017 to January 2018 using a randomized complete block design with three replications. Genetic materialused were 21 maize genotypes from the Indonesia Cereal Research Institute (ICERI) and IPB, including 19 hybrids and 2inbred lines. The results showed that the dry root weight under normal conditions had significant positive correlation withgrain yield under waterlogging stress, and therefore is potential for early screening. Adaptive genotypes in waterloggingstress selected based on dry root weight are DKLx30, DKLx11, MGoldx37, MGOldx41, and IPB L15-1xMR14. Predictedmean yield across these genotypes was 0.57 ton ha-1 higher yield than the overall mean in waterlogging stress condition.Selected hybrids can be further evaluated for variety release.